Acceptability Level of Crispy Malunggay Chips Among Selected Grade 12 Home Economics Students in Bestlink College of the Philippines A.Y 2021-2022: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Quick junk food consumption and its consequences have become a global public health concern because of its deteriorating health consequences and surging prevalence. Though its adverse health consequences are widely prevalent in all age groups, children and adolescents are more at risk. It may lead to obesity and be a risk factor for non-communicable diseases (NCDs) like heart diseases, cardiovascular disease, cancer, hypertension, diabetes, etc. We conducted this research because many young people and adults today are growing fonder of junk foods and getting less familiar with vegetables. This study aims to provide people with another alternative way to increase the consumption of the vegetable Malunggay by turning it into a delicious and healthy chip. We also aim to introduce a new way to enjoy the Malunggay vegetable in the chips. We also aim to increase the consumption of Malunggay vegetables. This research employs a quantitative descriptive design utilizing in-person survey-type questionnaires to gather information about the acceptability level of crispy malunggay chips among selected grade 12 Home Economics students in Bestlink College of the Philippines A.Y 2021-2022. According to Fluet (2021), descriptive research is a definitive quantitative method commonly used to evaluate certain hypotheses and characterize traits or functions. Thus, this design will be used since the main objective of this research is to know the acceptability level of crispy malunggay chips among selected grade 12 Home Economics students in Bestlink College of the Philippines.  Based on the result of the study, the researchers found the following: the acceptability level of Crispy Malunggay Chips in terms of having a good taste with a weighted mean of 4.34 and interpreted as Strongly Agree. Having a good colour with a weighted mean of 4.24, it is interpreted as Strongly Agree. In terms of aroma, with a weighted mean of 3.96, it is interpreted as Agree; in terms of texture, with a weighted mean of 4.24, it is interpreted as Strongly Agree. The acceptability level of having a healthy effect of eating Crispy Malunggay Chips with a weighted mean of 4.54 and interpreted as Strongly Agree. The acceptability level of gaining healthy benefits by consuming Crispy Malunggay Chips with a weighted mean of 4.36 and interpreted as Strongly Agree. The acceptability level of those who prefer Crispy Malunggay Chips over junk foods, with a weighted mean of 4.54, was interpreted as Strongly Agree. When we had the results from our surveys, which determine if Crispy Malunggay Chips is accepted by the grade 12 home economics students in Bestlink College of the Philippines A.Y 2021-2022, the mean score was interpreted to be acceptable to be eaten by the respondents. Crispy Malunggay Chips are acceptable in taste, colour, aroma, and texture. The respondents also accepted that eating Crispy Malunggay Chips will gain healthy benefits such as Vitamin C and Potassium, help your body heal, build muscle, and boost the immune system. Also, the respondents prefer the Crispy Malunggay Chips over the junk food. Therefore, we concluded that the Crispy Malunggay Chips are acceptable to the selected Grade 12 Home Economics Students in Bestlink College of the Philippines A.Y 2021-2022.
Keywords: acceptability; Keywords: acceptability; healthy benefits